The Clinical Significance of Light Chain Predominant Multiple Myeloma. (9th November 2022) - Arinze, Nkechi; Singh, Gurmukh
Abstract: Multiple Myeloma (MM) is a neoplastic clonal proliferation of terminally differentiated B- lymphocytes. It accounts for 1.6% of all cancers and about 10-15% of all hematological malignancies in the United States. Monoclonal immunoglobulins provide an indication of tumor burden in patients with plasma cell neoplasm. Recent development has shown that a proportion of intact immunoglobulin producing multiple myeloma secrete much higher amounts of free light chains than usual; i.e. light chain predominant multiple myeloma (LCPMM). About 18% of multiple myeloma secreting intact immunoglobulins secrete higher amount of free light compared to other intact immunoglobulin secreting myelomas and are associated with significantly poorer clinical outcomes. In this study, a retrospective investigation comparing the laboratory and clinical findings in conventional MM and LCPMM was undertaken. Three hundred and sixteen patients with conventional MM and seventy-one patients with LCPMM were studied. The results were remarkable for marked increase in death rate in the LCPMM group compared to the conventional MM group, 35.2% and 13.6% respectively; P-value .00001. The occurrence of dialysis was also markedly increased in the LCPMM group compared with the conventional MM; 18.3% vs. 3.5% P-value .00001. A markedly lower eGFR was observed in patients with LCPMM group compared to patients with conventional MM with an average value of 46.3 versus 69.4 ml respectively P value .0000003. In conclusion, light chain predominant plasma cell myeloma confers a significant disease burden, poor clinical outcomes and shorter survival. Further prospective trial will be helpful in understanding the pathogenesis, the course, and management of the disease. An assay for serum free monoclonal light chains has been described and could serve as a marker for minimal residual disease in such patients. We aim to further study the clinical impact of light chain predominant plasma cell myeloma (LCPMM) to increase the current knowledge of the disease and investigate therapeutic interventions.